Small contributions of dust to PM2.5 and PM10 concentrations measured downwind of Oceano Dunes. (1st February 2023) - Lewis, Savannah L.; Russell, Lynn M.; McKinsey, John A.; Harris, William J.
Abstract: The Oceano Dunes State Vehicular Recreation Area (ODSVRA) is a large natural source of wind-driven dust emissions that primarily consist of particulate matter (PM) for which most of the mass is greater than 1 μm. The San Luis Obispo County Air Pollution Control District (SLOAPCD) has targeted ODSVRA emissions to reduce exceedances of the state standard of 50 μg m −3 for PM smaller than 10 μm (PM10) at a coastal monitoring site located 1 mile downwind of the dune area. To evaluate the potential effectiveness of this abatement strategy, five sets of measurements were collected during the windy afternoons of high-wind months (May and October) from 2019 to 2021 to quantify the organic and elemental composition of PM10 and PM smaller than 2.5 μm (PM2.5) samples. The five-campaign average afternoon PM2.5 composition relative to Beta Attenuation Monitor (BAM) concentrations included 14 ± 12% dust, 9 ± 9% sea salt, 4 ± 5% non-sea salt sulfate, and 8 ± 8% organic components, with the difference between BAM and the measured components contributing the remaining 66 ± 16% unidentified components. The high afternoon unidentified contribution was partially attributable to water, consistent with the increasing relative humidity during warm afternoons, since there was a lower unidentified contribution for overnight samples. The remaining unidentified components are consistent with prior measurements of semivolatile contributions of ammonium nitrate and organic compounds constituting >40% of PM2.5 in central California. The organic functional group signature in Fourier Transform Infrared (FTIR) spectroscopy for PM2.5 was similar to previously reported ambient marine aerosol, consistent with a natural marine source for most of the organic mass concentration. For PM10, the dust fraction was 11 ± 8% of BAM PM10 concentration and increased to 14 ± 10% of BAM PM10 concentration during days in which hourly BAM PM10 concentration exceeded 140 μg m −3 . There was no statistically significant difference (p»0.05) between dust, sea salt, sulfate, or organic PM2.5 fractions between weekend and weekday concentrations, similar to prior findings for the region. These results are consistent with national and state assessments of the good air quality of the region and suggest that semivolatile components may cause differences between BAM and gravimetric mass concentrations for sampling times shorter than 24 h. In addition, the results demonstrate that the regulated dust abatement implemented at ODSVRA is misapplied and unlikely to improve downwind air quality significantly, since ODSVRA and other nearby sandy areas contribute only 14% of BAM PM10 and have not been shown to include toxic components. Highlights: Oceano Dunes mineral dust contributes an average of at most 14% of BAM PM10 measured downwind during windy afternoons. Average afternoon PM2.5 included 14 ± 12% dust, 9 ± 9% sea salt, 4 ± 5% non-sea salt sulfate, and 8 ± 8% organic components. Unidentified components are consistent with semivolatile contributions of ammonium nitrate and organic compounds.